Walerian Borowczyk jako dokumentalista surrealistyczny = Walerian Borowczyk as a surrealist documentary filmmaker - Prusinowski, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Famous film critic André Bazin classified a distinction between "those directors who put their faith in the image and those who put their faith in reality". The documentary output of Walerian Borowczyk, best known for his animated and feature films, seems difficult to fit into any of these categories. The author of this article analyses Borowczyk`s films as "Diptych" ("Diptyque", 1967), "A Private Collection" ("Une collection particuli?re", 1973), "Letter from Paris" ("Brief von Paris", 1976) and "The Greatest Love of All Times" ("L`amour - monstre de tous les temps", 1977). Those pictures are rare examples of surrealist ideas incorporated into documentary cinema.
Keywords: surrealizm; film dokumentalny; kino polskie; kino francuskie; surrealism; documentary film; French cinema; Polish cinema